World music unit in the general music classroom: hybrid approach to music teaching - Cechak, Andrea (Kansas State University, 2021)
The world music unit presented for this report has been specifically designed for a sixth-grade general music classroom setting, allowing students to participate both synchronously and asynchronously. World music is an ideal unit that demonstrates the widely known claim that music is an interdisciplinary subject. The primary focus for presenting this world music unit is to promote learners on becoming empathetic toward various cultures, as well as achieving the status of being a well-rounded student throughout all subject matters. The countries selected for this unit include Ireland, Japan, Ghana, and Mexico. These four consecutive lessons have students engaging in activities such as constructing a virtual passport, reflecting and dictating through written form, a time that students have heard music from a different part of the world, identifying factors that encompasses a specific cultural lifestyle, and listening, evaluating, responding to traditional music styles native to each culture. These lessons reflected a multi-modality approach so that full inclusivity could take place among all learners in the general music classroom setting. While completing course work for my Master’s degree, I have acquired invaluable experience and knowledge that have altered my daily classroom routine. Throughout the development of my personal music education philosophy, I was able to solidify my ideas on why music education should be present in a public-school setting. Researching and interpreting several music education philosophers allowed me to better understand that there is no one-size-fits-all music teaching approach and that each contributing philosopher in our history and philosophy of music education course, had something exceptional to state. Furthermore, each philosophical statement could be interpreted in a plethora of ways depending on a person’s current music teaching situation. The history and philosophy of music education course also allowed me the chance to reflect on daily lessons and methodology. I was able to settle on what skills I wanted my students to walk away with, which made me a stronger advocate for my program and gave me a stronger sense of well-being. Additionally, the curriculum development and assessment course was of great benefit while constructing lessons for the world music unit presented in this report. Although stringent restraints had been dictated to the music department by my specific school district, I was able to lay out a strong foundation on what exactly I wanted to cover in a very constraining time span. Constructing student-centered criteria, rubrics and checklists are resourceful tools with which I now feel confident. Understanding how to incorporate assessments within each classroom activity has validated to my school community that learning is happening each time students step into my classroom. These new assessment skills are also resourceful for presenting data to school boards and administration when again, advocating for a school music program.
Keywords: Hybrid teaching; Multicultural music; General music